An Analysis of Input-Output Inter Industry Linkages in the Malaysian Economy - Chiah, Shing Yih (Universiti Malaysia Sarawak (UNIMAS), 2016)
Economic sectors are closely linked to the rest of the economy through backward and forward linkages. This present paper intends to assess the interconnectedness in the production structure of the Malaysian economy, using the input-output analysis. In this research, Rasmussen unweighted and weighted approaches were applied to the Malaysian I-O table for the year 2010 using 50 aggregated sectors to identify the key sectors. The most contribution of this study is that it provides us a good tool in devising pragmatic policies so as to enhance the competitiveness of key economic sectors and establish a deeper economic linkage, thereby induce a greater rates of economic development.